Numerical modelling of the punching behaviour of steel fibre reinforced self-compacting concrete flat slabs - Barros, Joaquim A. O. (2013)
Punching shear failure on flat reinforced concrete slabs of residential and commercial buildings is generally avoided by using transversal reinforcement and/or chapiters. The first option requires intense labour, mainly when densely flexural reinforcement exists in the potential punching failure region, with detrimental consequences in terms of costs of this construction solution. The second option has also extra costs due to the necessity of special arrangements of moulds for casting the chapiters. The interference of a chapiter on the flatness of the slab can also be a negative aspect from the architectonic point of view. The use of steel fibre reinforcement can be a solution to avoid both the conventional punching reinforcement and chapiters. Therefore, an experimental program was carried out to assess the potentialities of steel fibre reinforced self-compacting concrete (SFRSCC) for the punching resistance of flat slabs centrically loaded. This experimental program is described, and the main results are presented and analysed. To assess the potentialities of the Reissner-Mindlin FEM-based theory for modelling the behaviour of flat SFRSCC slabs submitted to punching loading configuration, new features were introduced in the out-ofplane shear constitutive law of the SFRSCC. These features are briefly described and the main focus was given on the modelling strategy adopted for simulating the punching tests.